Innovation, trade, and finance - Peter Egger; Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper proposes a model where heterogeneous firms choose whether to undertake R&D or not. Innovative firms are more productive, have larger investment opportunities and lower own funds for necessary tangible continuation investments than non-innovating firms. As a result, they are financially constrained while standard firms are not. The efficiency of the financial sector and a country's institutional quality relating to corporate finance determine the share of R&D intensive firms and their comparative advantage in producing innovative goods. We illustrate how protection, R&D subsidies, and financial sector development improve access to external finance in distinct ways, support the expansion of innovative industries, and boost national welfare. International welfare spillovers depend on the interaction between terms of trade effects and financial frictions and may be positive or negative, depending on foreign countries' trade position.
Keywords: F11; G32; L26; O38; 330; innovation; financial development; R&D subsidies; protection; Innovation; Industrielle Forschung; Innovationspolitik; Wohlfahrtseffekt; Internationaler Wettbewerb; Mehr-Sektoren-Modell; Theorie